Dermatological manifestations in Noonan syndrome. (1st June 2019) - Bessis, D.; Miquel, J.; Bourrat, E.; Chiaverini, C.; Morice‐Picard, F.; Abadie, C.; Manna, F.; Baumann, C.; Best, M.; Blanchet, P.; Bursztejn, A.‐C.; Capri, Y.; et al.
Summary: Noonan syndrome (NS) is a genetic disorder affecting up to 1 in 1000 people. It is recognised by an unusual facial appearance, heart defects and small stature. Some people with features of NS also have lots of small dark brown flecks on their skin (lentigines), a condition formerly known as LEOPARD syndrome but now called NS with multiple lentigines (NSML). There are also some atypical (unusual) "Noonan‐like" syndromes: this overlapping group of "Rasopathies" also includes Costello syndrome and cardio‐facio‐cutaneous syndrome. About 10 genes responsible for these conditions are now known, but the dermatological (skin) features of the different genetic types have never been clearly defined. Therefore, these French doctors, based at 10 different hospitals, systematically recorded the skin abnormalities seen in patients with any kind of NS attending their clinics over a 4‐year period, and correlated them with NS subtype and gene. Of 129 patients, aged from 9 months to 77 years, three quarters had mutations (changes) in the PTPN11 gene and of these 65 were diagnosed as NS and 34 as NSML. Dermatological features in the NS patients were mild and non‐specific such as easy bruising, raised hair follicles (keratosis pilaris), lax skin or wavy hair. NSML patients additionally had dozens of lentigines, larger brown patches and usually had particular PTPN11 mutations. NS patients with mutations in a different gene were more likely to have striking skin features including unusually curly hair, sparse eyebrows, marked keratosis pilaris or multiple moles. This research highlights the value of careful dermatological documentation in patients with genetic syndromes.